The impact of different sources of fatty acids on the fetal programming of atherosclerosis - Gates, L. J. (2021)
Maternal hypercholesterolaemia has been associated with atherosclerosis in the offspring of humans and animal models. Partially hydrogenated vegetable oil (P) and ruminant milk fat (R) contain trans fatty acids (TFA) that differ in isomer distribution and cause changes to cholesterol metabolism. TFAs are passed to the offspring across the placenta during fetal development and via the mother’s milk. The study aimed to assess whether maternal consumption of two types of TFA diet (P and R) and a diet rich in saturated fatty acids (“Western” W diet) would differentially alter maternal lipoprotein metabolism causing changes to the offspring’s lipoprotein metabolism and increasing their susceptibility to atherosclerosis in adulthood. Experimental fat diets were fed to female C57BLJ6 mice during pregnancy (PC, RC, or WC), or throughout pregnancy and lactation (PP, RR, WW). Female offspring carrying the human ApoE*3 Leiden gene (AEL) were weaned onto post-natal diets for 12 weeks: (i) Chow (CCC, PCC, RCC); (ii) Atherogenic (CCA, PCA, PPA, RCA, RRA, WCA, WW); (iii) or remained on their dams’ allocated fat diet (PPP, RRR or WWW). Maternal and offspring serum lipoprotein concentrations were measured, and offspring atherosclerosis assessed by lipid staining in cross sections of aorta. At day 17 gestation, dams consuming P diet had increased serum total cholesterol and triacylglycerol concentrations compared to R dams. Dams that had consumed P or R during pregnancy and C during lactation had similar serum cholesterol concentrations. However, continuing the fat diet throughout lactation caused R dams to have significantly greater serum cholesterol compared to P, W, and C dams. Dams consuming P and R had diet specific trans isomers in their adipose tissue, indicating the developing fetus and neonate were exposed to different TFA isomers. Maternal TFA consumption during pregnancy appeared to protect offspring from atherosclerosis in later life, irrespective of isomeric distribution of the TFA, however this effect was lost if the TFA diet was continued to be fed during lactation and early development periods. In conclusion, maternal consumption of TFA and SFA diets did not increase susceptibility of offspring to atherosclerosis. Both R and P TFA diets during pregnancy had an athero-protective effect. There was no effect of maternal W diet on offspring atherosclerosis.